From Genome to Drugs: New Approaches in Antimicrobial Discovery - Serral, Federico; Castello, Florencia A.; Sosa, Ezequiel J.; Pardo, Agustín M.; Palumbo, Miranda Clara; Modenutti, Carlos; Palomino, María Mercedes; Lazarowski, Alberto; Auzmendi, Jerónimo; Ramos, Pablo Ivan P.; Nicolás, Marisa F.; Turjanski, Adrián G.; et al. (Frontiers in Pharmacology, 2021)
The decades of successful antibiotics use is currently challenged by the emergence of increasingly resistant bacterial strains. Novel drugs are urgently required but, in a scenario where private investment in the development of new antibiotics is declining, efforts to combat drug-resistant infections are becoming a worldwide public health problem. The reasons for the unsuccess of new antimicrobial development projects range from inadequate selection of the molecular targets to lack of innovation. In this context, increasingly available omics data for multiple pathogens has created new opportunities for drug discovery and developments to fight infectious diseases. Identification of appropriate molecular targets is currently accepted as a key step of the drug discovery process. In this sense, diverse layers of multi-omics data in conjunction with structural/functional analysis and system biology can be used to prioritize the best candidate proteins. Once the target is selected, virtual screening can be used as a powerful methodology to explore molecular scaffolds that could act as inhibitors leading to new drug development lead compounds. This review focuses on how the advent of omics and the development and application of bioinformatics strategies lead to a ‘big-data era’ that improves target selection and lead compound identification in a cost-effectively shortened timeline.